Relationships among jumping performances and sprint parameters during maximum speed phase in sprinters - Kale, M.; Asci, A.; Bayrak, C.; Acikada, C. (The Journal of Strength and Conditioning Research, 2009)
The purpose of this study was to investigate the relationships among jumping performances and speed parameters during maximum speed phase in sprinters. Twenty-one men sprinters volunteered to participate at the beginning of the preparation training phase. All tests-including 100-m sprint running, squat jump (SJ), countermovement jump (CMJ), drop jump (DJ), 60-second repetitive jump (RJ), standing long jump (SLJ), standing triple jump (STJ), standing quintuple jump (SQJ), and standing 10-stride jump (STENJ)-were done on switching mats. Flight (FT) and contact times (CT) during the vertical jump tests and 10-m split times during 100-m sprint running were measured by a 2-channel precision timing system (PTS) connected to the mats. The trace marking method was used for measuring the stride length (SL) through 60 m in 100-m sprint running. Stride frequency (SF), maximum velocity (Vmax), jump height for all vertical jumps, and lower-body power in DJ and RJ were calculated. Statistical analysis showed that the highest significant correlation was found between Vmax and DJ height (r = 0.69; p < 0.05). However, the lowest significant correlation coefficient was found between SL at maximum velocity phase of sprint running and SJ (r = 0.39; p < 0.05). In conclusion, DJ height is demonstrated to be a more effective way to reflect Vmax during sprint running than the other vertical and horizontal jump tests at the beginning of the preparation training phase.